The Physicochemical Characteristics of Ibiekuma River Ekpoma, Nigeria - Omotoriogun, Taiwo Crossby; Uyi, Osariyekemwen Osa; Egbon, Ikponmwosa Nathaniel (Journal of Wetlands Ecology, 2012)
The Ibiekuma River is an important source of livelihood to its catchment. It contributes enormously to research success and living standard of students and staffs of the Ambrose Alli University Ekpoma, Nigeria. The aim of the study was to determine the impact of anthropogenic activities on the physicochemical properties of Ibiekuma River. Twenty seven water samples were collected at four stations during the study period and analyzed accordingly. The results obtained shows that the physicochemical parameters of the river were in conformity with the World Health Organization (WHO), National Agency for Food, Drug Administration and Control (NAFDAC) and Nigerian Industrial Standard (NIS) safe limits, except for pH values which ranged from 4.69 to 4.81. The heavy metal concentrations were found to be within the limit of the guidelines prescribed by WHO and NAFDAC. Also, there was no significant difference (P > 0.05) in the concentrations of the physicochemical parameters across the four stations sampled along the Ibiekuma River. Water obtained from Ibiekuma River will be fit for domestic use, only if purified. DOI: http://dx.doi.org/10.3126/jowe.v6i0.5242 J Wet Eco 2012 (6): 01-06